Criminalization Of Cohabitation In The National Criminal Code And The Problems Of Proving It According To The 2025 Criminal Procedure Law: Reconstruction Of The Element Of “Living Together As Husband And Wife” From A Fair Trial Perspective - Wildan Ambron Ritonga; Aditiarman Aditiarman; Aditya Kusuma Sumantri; Beni Setiawan; Fanita Aditia (JURNAL HUKUM SEHASEN, 2026)
Cohabitation is a social reality in the form of cohabitation between two people as a married couple without a legally recognized marital bond. Law Number 1 of 2023 concerning the Criminal Code criminalizes it through Article 412, but the formulation of “living together as husband and wife outside of marriage” leaves the issue of conceptual boundaries, duration, patterns of domestic relations, and space for state intervention in private life. This research discusses two problems: the regulation of cohabitation crimes in the National Criminal Code and the construction of proof according to Law Number 20 of 2025 concerning the Criminal Code. The research uses normative legal methods with limited legislative, conceptual, and comparative approaches, through a prescriptive analysis of primary legal materials and eighteen attached scientific articles. The results of the study show that Article 412 is a complaint offense that has a formal character and continues, so it is not enough to prove the existence of two people in one place or the alleged intercourse. The elements of delinquency must be built from the continuity of residence, the establishment of a factual household, social representation as a couple, and the absence of a valid marriage. The 2025 Criminal Code expands evidence through Article 235 and recognizes electronic evidence in Article 242, but also requires authentication, legality of acquisition, and judicial testing. The study concluded that the effectiveness of Article 412 enforcement depends on layered evidentiary standards that limit speculation, protect privacy, and prevent criminalization based on moral prejudice.